CuCo2S4 Nanoparticles Embedded in Carbon Nanotube Networks as Sulfur Hosts for High Performance Lithium-Sulfur Batteries - Hongying Wang; Yanli Song; Yanming Zhao; Yan Zhao; Zhifeng Wang (Nanomaterials, 2022)
Rational design of sulfur hosts for lithium-sulfur (Li-S) batteries is essential to address the shuttle effect and accelerate reaction kinetics. Herein, the composites of bimetallic sulfide CuCo2S4 loaded on carbon nanotubes (CNTs) are prepared by hydrothermal method. By regulating the loading of CuCo2S4 nanoparticles, it is found that when Cu2+ and CNT are prepared in a 10:1 ratio, the CuCo2S4 nanoparticles loaded on the CNT are relatively uniformly distributed, avoiding the occurrence of agglomeration, which improves the electrical conductivity and number of active sites. Through a series of electrochemical performance tests, the S/CuCo2S4-1/CNT presents a discharge specific capacity of 1021 mAh g−1 at 0.2 C after 100 cycles, showing good cycling stability. Even at 1 C, the S/CuCo2S4-1/CNT cathode delivers a discharge capacity of 627 mAh g−1 after 500 cycles. This study offers a promising strategy for the design of bimetallic sulfide-based sulfur hosts in Li-S batteries.